2018
DOI: 10.1080/02688697.2018.1429569
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endoscopic versus microscopic trans-sphenoidal surgery for large pituitary adenoma

Abstract: ETS is superior to MTS in treatment of large pituitary adenomas with comparable post-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These results compare favorably with the published literature, where the rate of postoperative CSF leaks ranges from 1% to 6% 26 and other serious complications are rare, with no evidence of increase in complication rate compared to series without use of iMRI. 9,26,27 Overall, our findings support the general advantages of the endoscopic over the microscopic approach and augmented results with iMRI. iMRI inevitably adds to the operative time, estimated to be approximately 45-60 minutes, although evolving workflows have reduced time requirements, and iMRI often eliminates the need for postoperative MRI prior to discharge.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results compare favorably with the published literature, where the rate of postoperative CSF leaks ranges from 1% to 6% 26 and other serious complications are rare, with no evidence of increase in complication rate compared to series without use of iMRI. 9,26,27 Overall, our findings support the general advantages of the endoscopic over the microscopic approach and augmented results with iMRI. iMRI inevitably adds to the operative time, estimated to be approximately 45-60 minutes, although evolving workflows have reduced time requirements, and iMRI often eliminates the need for postoperative MRI prior to discharge.…”
Section: Discussionsupporting
confidence: 76%
“…7 In secretory tumors, particularly with adrenocorticotropic hormone (ACTH), even small residual tumors can be associated with high rates of morbidity. 8 Although reported resection rates are generally higher in patients treated endoscopically compared with microscopically, 5,9 concern has been raised regarding the potential increased risk of endocrine deficits and CSF leaks.…”
mentioning
confidence: 99%
“…Treatments such as radiotherapy or stereotactic radiosurgery may be offered to those patients who don't benefit from surgery. 2 Transsphenoidal surgery for pituitary adenomas has a very low incidence of complications and even lower mortality. Transient diabetes insipidus due to CSF leak and post-op hematoma is a complication that is apprehended.…”
Section: Introductionmentioning
confidence: 99%
“…However, in increased tumor size, the success rate can be lower in both approaches owing to lateral extension and invasion of the cavernous sinus. 2,5 Pituitary adenomas were most effectively addressed and the treatment was most rewarding when it is detected early followed by rendering prompt and relevant treatment. In another study, it has been concluded that endoscopic transsphenoidal surgery is an effective and safe modality for pituitary adenoma's treatment and can be employed as a first-choice therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Except for lactating pituitary adenomas, surgical resection is the first choice of treatment, and most pituitary adenomas can be removed by transsphenoidal surgery. At present, resection of pituitary adenomas by transsphenoidal approach under microscopy and neuroendoscopy is a clinically mature minimally invasive surgery[5].…”
Section: Introductionmentioning
confidence: 99%